Three-dimensional finite element analysis of braced excavation systems - Winata, Berlina Margaretha. (2011)
Braced excavation study is usually modeled using plane strain (two-dimensional) finite element analysis. In this kind of analysis, the length of excavation wall is assumed to be infinitely long, so that the effect of the length of excavation is neglected. However this analysis may not correctly represent the actual scenario of the braced excavation system, especially for the excavation in which the wall length is short. In this report, a three-dimensional finite element parametric study which includes 24 finite element simulations with varied excavation length and wall system stiffness is conducted to examine the effect of excavation geometry on the performance of braced excavation system in a typical Singapore soft clay soil profile. The aspects that are examined are the wall lateral movements, bending moments, lateral earth pressure and strut loads. In addition, analyses were also carried out to study the distribution of strut forces after the failure of the lowest strut. Comparisons between plane strain and three-dimensional analyses are carried out in terms of the plane strain ratio (PSR). PSR is defined as the ratio of maximum lateral movement behind the primary wall between plane strain and three-dimensional finite element analyses. The results show that for flexible and medium flexible walls, when the ratio of excavation length to the excavation height and to the excavation width is greater than 3 and 2.5 respectively, the wall lateral movements from three-dimensional analysis agree with the results from plane strain analysis provided that the excavation height and width are constant. However no clear conclusions can be drawn for the case of stiff walls. The results also show that majority portion of the failed strut force is distributed to other adjacent struts instead of only to the strut immediately above it as assumed in plane strain analysis.